The association between COVID-19 and muscle strain injury occurrence in elite soccer players: a prospective study - Wezenbeek, E.; Denolf, S.; Pieters, D.; Bourgois, J.; Philippaerts, R.; Winne, B.; Schuermans, J.; Witvrouw, E. (British Journal of Sports Medicine, 2021)
Background Because of the high injury rate currently seen in soccer players and the exceptional pandemic circumstances, the question arises to what extent this reported increase in injury incidence is associated with COVID-19.